2011
DOI: 10.1136/annrheumdis-2011-200352
|View full text |Cite
|
Sign up to set email alerts
|

Enthesis erosion in spondyloarthritis is not a persistent structural lesion

Abstract: US examination of Achilles erosions is reliable and sensitive to change. An association was found between Achilles erosions and objective activity-based measurements of SpA outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
0
5
1
2
Order By: Relevance
“…In particular, erosion seems to be an indicator for enthesis US in disease activity. De Miguel et al reported that Achilles erosion had a signi cant association with objective disease activity in spondyloarthritis [29]. In addition, there was no signi cant difference in the calci cation score between the AS and control groups in the results of the present study.…”
Section: Discussioncontrasting
confidence: 43%
“…In particular, erosion seems to be an indicator for enthesis US in disease activity. De Miguel et al reported that Achilles erosion had a signi cant association with objective disease activity in spondyloarthritis [29]. In addition, there was no signi cant difference in the calci cation score between the AS and control groups in the results of the present study.…”
Section: Discussioncontrasting
confidence: 43%
“…Recent studies have indicated that ultrasound may accurately predict which patients will go on to develop SpA . In one investigation, ultrasound examination of Achilles erosions correlated with objective activity‐based measurements of SpA outcomes, and was sensitive to change . In the study by D'Agostino and colleagues described above, vascularized enthesis as detected by PDUS combined with Amor's criteria proved to be the only independent contributors to a diagnosis of SpA .…”
Section: Imaging Of the Enthesismentioning
confidence: 97%
“…US proved to be sensitive to change when monitoring enthesis erosions at 6 and 12 months and the method is a useful tool for assessing these kinds of modifications [76].…”
Section: Enthesitis Ultrasound and Disease Activity Monitoringmentioning
confidence: 99%